OPTIMIZING EARLY CHILDHOOD SEX EDUCATION TO PREVENT SEXUAL ABUSE IN PAUD AL-IRSYAD AL-ISLAMIYAH JEMBER - Siti Hamidahtur Rofi’ah; Badrun Fawaidi (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to describe the application of sex education for early childhood to prevent sexual abuse in PAUD Al-Irsyad Al-Islamiyah Jember. This study used a qualitative descriptive case study type approach. Data collection techniques in this study were carried out by several means of observation, interviews and documentation. Researchers used data analysis which was carried out interactively. According to Miles, Huberman, and Saldana, data analysis that is carried out interactively must go through a process of condensing data, presenting data and drawing conclusions. The validity of the data in this study used source triangulation and method triangulation. The results showed that the introduction of sex education for early childhood to prevent sexual abuse in PAUD Al-Irsyad Al-Islamiyah Jember by: introducing children to the anatomy of their body parts, and explaining the function of each part in simple language, building positive habits and instilling the importance of protecting the organs particular body, this is integrated with the religious values ​​contained in the hadith. The media used are media pictures, stories, film screenings, toilet training, parenting and so on. The applications include: 1) Toilet training, 2) Instilling religious moral values ​​by introducing male and female genitalia and the obligation to cover them. 3) Parenting seminars held once or twice a month, 4) Introduction to body anatomy and its functions. 5) Teaching sex education with media images, 6) Application of regional regulations on Muslim/Muslim clothing.